PropTech in the Saudi real estate market: Case studies of NEOM and Qiddiya - Hechmi, Soumaya (Edelweiss Applied Science and Technology, 2025)
This study offers a comprehensive analysis of the rapid expansion of Property Technology (PropTech) in Saudi Arabia, positioning it as a strategic enabler for the nation’s Vision 2030 objectives of economic diversification and digital transformation. Utilizing a mixed-methods approach centered on in-depth case studies of the NEOM and Qiddiya giga-projects, this research is further supported by market analysis, technical appraisals, and policy assessment. The investigation focuses on critical dimensions, including technological deployment strategies, global benchmarking, projected socioeconomic impacts, and systemic implementation barriers. Findings highlight Saudi Arabia’s distinct capacity for mass adoption of PropTech, driven by unprecedented government incentives and sovereign wealth fund investment. Conversely, the study also identifies persistent challenges, such as regulatory lag, cybersecurity vulnerabilities in interconnected systems, and infrastructural gaps that could hinder inclusive access. This paper contributes to smart urbanism literature by demonstrating how resource-rich economies can leverage technology for urban development. Finally, it offers concrete, actionable recommendations for policymakers aimed at navigating the complexities of Saudi Arabia’s rapidly evolving real estate technology landscape and ensuring its sustainable growth.